Temperature and Humidity Control of the Tunnels in the Dam Using Wireless Sensor Networks - Dogan, Resul; Erdem, Ebubekir (Ieee, 2015)
The safety of dams is closely associated with that of people due to the fact that dams are directly linked to places where people live. The constant monitoring of dams through sensors and the prevention of problems through prediction are of vital importance for the safety of dams. Therefore, in order to determine the average temperature and humidity of an environment, temperature and humidity values coming from several sensors deployed in the environment must be processed. In this study, in an effort to properly operate reliable equipment in the tunnels of dams, TelosB sensor nodes by the Memsic Company, which supports wireless sensor network technologies and has a good coordination with the TinyOS embedded operating system, were placed in different sections of the tunnels in the dam of our research. These nodes were programmed based on the tree topology by using of the aforementioned operating system. Subsequent to the setup of the wireless sensor networks, the control of temperature and humidity was accomplished by monitoring respective values with the help of an interface.
19th IEEE International Conference on Intelligent Engineering Systems (INES) -- SEP 03-05, 2015 -- Bratislava, SLOVAKIA
Keywords: Wireless sensor networks; TinyOS; sensor node; control of temperature and humidity